Determinants of Kuala Lumpur Composite Index (KLCI) towards stock market return in Malaysia / Norman Helmi Ahmad Naim - Ahmad Naim, Norman Helmi (2022)
This paper investigate the significant relationship between the Kuala Lumpur Composite Index Stock Market Return and various macroeconomic factors such as oil price, exchange rate, interest rate, and inflation. This study used multiple regression model to analyze the significant relationship between the dependent variables and independent variables which is KLCI stock market return with macroeconomic determinants. A total of four indicators were taken as the independent variables of this study with a period of six(6) years monthly data from 2015 to 2020. Hence, this study shows that various macroeconomic factors such as interest rate and exchange rate have a significant relationship on the KLCI return. For this study, it used time-series data to analyze the significant relationship between various factors and stock market return. The result in this study shows that, three out of four independent variable have significant relationship and positive relationship with the dependent variables. Oil price, exchange rate and inflation have insignificant relationship with KLCI stock market exchange. Meanwhile, interest rate have significant relationship and negative relationship with KLCI stock market return.